Unreinforced and confined masonry buildings in seismic regions : validation of macro-element models and cost analysis - Marques, Rui Filipe Pedreira (2014)
Modern design of buildings requires accounting for sustainability aspects using a life-cycle perspective, but also the early design phase where earthquake actions have a significant influence concerning the structural design. Recently, the seismic evaluation of masonry buildings using macro-element modeling approaches became popular, by applying performance-based assessment procedures through nonlinear static (pushover) analysis methodologies. This work addresses the validation for these approaches referring to two full-scale masonry structures tested under quasi-static lateral loading and almost unknown in the literature. The experimental behavior of tested unreinforced masonry (URM) and confined masonry (CM) structures is compared against the pushover response of the corresponding computational models. Then, referring to typical housing in southern Europe and its usual design with a reinforced concrete (RC) structure, the validated assessment tools are employed to evaluate the earthquake-resistant possibilities of URM and CM solutions, namely in terms of maximum applicable ground accelerations. The masonry solutions are also compared in terms of construction costs against the RC typology. The considered analysis tools present a good agreement when predicting, satisfactorily, the experimental test behavior, thus being able to be used in performance-based design. With respect to the studied housing, the predicted pushover responses for the masonry structures denote capacity to resist earthquakes adequately. These structures allow also a significant cost reduction (up to 25%) against the RC, thus appearing to be competing alternatives.